Pursuing Impactful Entrepreneurship Research Using Artificial Intelligence - Lévesque, Moren; Obschonka, Martin; Nambisan, Satish (Entrepreneurship Theory and Practice, 2022)
It is time for the entrepreneurship field to come to terms with leading-edge artificial intelligence (AI). AI holds great promise to transform entrepreneurship into a more relevant and impactful field, but it must overcome conflicts between the AI-driven research approach and that of the traditional, theory-based research process. We explore these opportunities and challenges and suggest concrete approaches that entrepreneurship researchers can use to harness the power of AI with rigor and enhance research relevance. We conclude that incorporating the power of AI in entrepreneurship research and managing the associated risks offer a new and “grand challenge” for the field.